ADVERSITY QUOTIENT AND RESILIENCE IN MATHEMATICAL PROOF PROBLEM-SOLVING ABILITY - Fauziah Hakim; Murtafiah Murtafiah (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Abstract:Various mathematical abilities require a high level of struggle to be achieved, one of which is the ability to solve mathematical proof problems. Several factors are also associated with this ability, including adversity quotient and resilience. This research aimed to look at the effect of adversity quotient and resilience on the mathematical proof problem-solving ability. This research used a quantitative approach with a correlational method. The sample in this study were 31 students randomly selected from all students of the Mathematics Education Study Program at Universitas Sulawesi Barat who programmed Abstract Algebra course in the academic year of 2019/2020, amounting to 71 students. The analysis technique used is multiple linear regressions. The results of hypothesis testing indicate that adversity quotient and resilience affect the mathematical proof problem-solving ability positively both individually and simultaneously.Abstrak:Berbagai kemampuan matematis memerlukan daya juang tinggi untuk berhasil dicapai, salah satunya kemampuan pemecahan masalah pembuktian matematis. Beberapa faktor pun dikaitkan dengan kemampuan tersebut, antara lain adversity quotient dan resiliensi. Penelitian ini bertujuan untuk melihat pengaruh adversity quotient dan resiliensi terhadap kemampuan pemecahan masalah pembuktian matematis. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel pada penelitian ini sebanyak 31 mahasiswa yang dipilih secara acak dari seluruh mahasiswa Program Studi Pendidikan Matematika Universitas Sulawesi Barat yang memprogramkan mata kuliah Struktur Aljabar tahun akademik 2019/2020 yang berjumlah 71 mahasiswa. Teknik analisis yang digunakan adalah regresi linear berganda. Hasil pengujian hipotesis menunjukkan bahwa adversity quotient dan resiliensi berpengaruh positif terhadap kemampuan pemecahan masalah pembuktian matematis baik secara sendiri-sendiri maupun secara simultan.